The Effect of Using Short Movies on The Eleventh Grade Students’ Listening Comprehension Achievement - Darmawan Aldi Prakoso; Zakiyah Tasnim; Aan Erlyana Fardhani (EFL Education Journal, 2021)
This research was intended to find the effect of using short movies on the eleventh grade students’ listening comprehension. The research design used was quasi-experimental research design with non-equivalent class post-test design. The research context was purposive methods. The research participant was eleventh grade students of SMAN Kalisat. The data collection method was an English listening test with multiple choice and true-false question format. The result of the analysis showed that the test had high content validity with the percentage of 100% valid items. The test also very reliable with the reliability index 0.927 based on Guttman Split-Half Coefficient. The result of difficulty index of the try out test showed that in the multiple choice questions there were 3 items categorized as easy, 17 items were categorized as fair, and 5 items were categorized as difficult. In the true/false questions there are 3 items categorized as easy, 10 items were categorized as fair items, and 2 items were categorized as difficult. The T-test with equal variances assumed, t=-3,686 and p=0,002(<0,05) showed significant difference in the means between two classes. The result of the analysis showed that the null hypothesis (H0) was rejected, meanwhile the alternative hypothesis (H1) was accepted. It means there was a significant effect between the experimental and control class after they received different treatment.